(untitled) (Journal of Forest and Livelihood, 2003)
This paper summarizes the findings of a socio-economic baseline study undertaken amongst four Forest User Groups (FUGs) in Nepal focusing on levels of participation, understanding of, and benefit from, community forestry activities. Poorer households were found to benefit significantly less than wealthier households, and in some cases may even be directly disadvantaged by the advent of community forestry in their villages. A major cause of this inequity is that FUG committees are dominated by wealthier households. In addition, awareness levels of a range of community forestry and FUG institutional issues is low, particularly amongst the poorest groups. Forests are being managed below their productive potential and only a limited proportion of members’ forest product needs come from community forests.